2019
DOI: 10.1088/1757-899x/632/1/012089
|View full text |Cite
|
Sign up to set email alerts
|

Roughness of holes in metal and polymer composite bags

Abstract: The article presents the results of the research on the influence of cutting modes on the parameters of surface roughness during finishing of holes in mixed packages containing composite and metal materials. The object of the study is a mixed package containing layers of polymer composite material (CFRP), as well as layers of titanium and aluminum alloys. The main technological equipment used in the study is an automatic drilling machine. Cutting tool -carbide six-toothed reamer. For carrying out of researches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…From the ANOVA results in Table 4, it was found that the change in spindle speed affects the surface roughness to a much lower degree than the feed rate. 111 Nevertheless, the use of cryogenic coolant had the most significant contribution with 83.59% and 62.82% for R a and R z , respectively. It can be also observed that the order of the importance for the controllable cutting factors when drilling GFRPs is feed rate followed by spindle speed which is in agreement with previous studies.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…From the ANOVA results in Table 4, it was found that the change in spindle speed affects the surface roughness to a much lower degree than the feed rate. 111 Nevertheless, the use of cryogenic coolant had the most significant contribution with 83.59% and 62.82% for R a and R z , respectively. It can be also observed that the order of the importance for the controllable cutting factors when drilling GFRPs is feed rate followed by spindle speed which is in agreement with previous studies.…”
Section: Resultsmentioning
confidence: 94%
“…From the ANOVA results in Table 4, it was found that the change in spindle speed affects the surface roughness to a much lower degree than the feed rate. 111 Nevertheless, the use of cryogenic coolant had the most significant contribution with 83.59% and Table 4. ANOVA analysis of cutting forces, surface roughness parameters and delamination factors at entry and exit sides.…”
Section: Surface Roughness Analysismentioning
confidence: 98%